2021
DOI: 10.1287/orsc.2020.1427
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Engagement as Practice: A Study of the Attentional Infrastructure of Healthcare Chief Executive Officers

Abstract: In this paper, we investigate the attentional engagement of chief executive officers (CEOs) of large healthcare organizations in England. We study attention ethnographically as something managers do—at different times, in context, and in relation to others. We find that CEOs match the challenges of volume, fragmentation, and variety of attentional demands with a bundle of practices to activate attention, regulate the quantity and quality of information, stay focused over time, and prioritize attention. We call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 55 publications
1
42
0
Order By: Relevance
“…Identifying the conditions under which strong normative and interpersonal integration are generated across systems will be vital. Such efforts might focus on leadership, as past research has suggested that leaders play a central role in setting norms (Opp, 1982; Taggar & Ellis, 2007), facilitating change when cultures become dysfunctional (Schein, 2010), establishing productive team climates (Nembhard & Edmondson, 2006), and setting the attentional infrastructure of their organizations (Nicolini & Korica, 2021). However, much of this existing scholarship has focused on single organizations and top-level leadership.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the conditions under which strong normative and interpersonal integration are generated across systems will be vital. Such efforts might focus on leadership, as past research has suggested that leaders play a central role in setting norms (Opp, 1982; Taggar & Ellis, 2007), facilitating change when cultures become dysfunctional (Schein, 2010), establishing productive team climates (Nembhard & Edmondson, 2006), and setting the attentional infrastructure of their organizations (Nicolini & Korica, 2021). However, much of this existing scholarship has focused on single organizations and top-level leadership.…”
Section: Discussionmentioning
confidence: 99%
“…the 'when' of situated attention). This resonates with a recent, pioneering study of Nicolini and Korica (2021) considering attention allocation as a practice. Thus, our arguments give rise to a new perspective on the ABV, which has mainly been considered from an information-processing perspective, highlighting limited attentional capacity (e.g.…”
Section: Implications For Future Research On Situated Attentionmentioning
confidence: 52%
“…Indeed, practices are enacted in specific circumstances and these circumstances matter. The way practices are enacted is shaped by social dynamics, that is, the relationship among different actors (Feldman & Orlikowski, 2011;Nicolini & Korica, 2021), but also the material conditions under which they are performed; be it the physical environment of a location or the characteristics of a particular tool or piece of software (e.g. Jarzabkowski et al, 2013).…”
Section: Towards a Research Agenda Of Situated Attention: The Role Of...mentioning
confidence: 99%
See 2 more Smart Citations